Assessing the eco-environmental aspects of fossil fuels-based units substitution of Point Aconi thermal power plant by green-based energies: a case study of Canada - Nima Amiri (21842687) (2024)
Canada possesses significant potential in harnessing renewable energy from its vast and diverse geography, which can generate clean electricity. This paper presents a model that replaces fossil fuels used in a proposed thermal power plant in Point Aconi, Nova Scotia, with photovoltaic and wind turbine units based on the region’s climate conditions. The research results are based on evaluating multiple thermal power plants worldwide and examining various wind turbines and PV panels from different companies to ensure accuracy. The chosen units that best suit the location’s geographical and biological conditions, transmission, and operation costs demonstrate that the power plant currently consumes approximately 47 tons of coal and petroleum coke per hour. Replacing these materials with the proposed green units makes it possible to reduce environmental pollution by eliminating almost 165 tons of CO2 and other pollutants per hour while increasing the plant’s efficiency and independence from fossil fuel price variations. The presented structure’s ROI is approximately 20 years, which is reasonable compared to the economic and environmental benefits of utilizing such a structure and converting the thermal power plant to green units. Other Information Published in: Electrical Engineering License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00202-024-02482-w